Implementasi Peraturan Bupati Gayo Lues Nomor 28 Tahun 2013 Tentang Pemberian Hibah dan Bantuan Sosial kepada Masyarakat di Kabupaten Gayo Lues Tahun 2020 - Bintang Bintang; Heri Kusmanto; Adam Adam (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
This study aimed to ascertain the implemtation of the program of grants and social assistance in Gayo Lues, knowing what factors influence the implementation of grants and social assistance in Gayo Lues,, and to identify bottleneks in the delivery mechanism of grants and social assistance in Gayo Lues. The method used is descriptive qualitative, in depth interviews with research intrument. The result of this study are Policy Impelementation grants and social assistance in Gayo Lues went pretty smoothly. Although it still has not been done in accordance with the laws in force but nearly all stages of proposal and grants management activities and social assistance have been implemented. Then some of the factors that affect the implementation of the grants program and social assistence is communication, resource capabilities, attitudes executor, bureaucratic structure, and the size and environmental policy objectives. Obstacles encountered in the mechanism of providing grants and social assistance in Gayo Lues less that optimal, the implementation of social assistance program and grant the use data of beneficiaries of grants and social aid the previous years, and many recipients aid that has not verified that factual data, there is still overlap in the distribution of grant and social assistance, socail assistance funds even impressed educate people corrupt and nepotism.